2018
DOI: 10.1111/famp.12360
|View full text |Cite
|
Sign up to set email alerts
|

Mother‐Stepfather Coparenting in Stepfamilies as Predictor of Child Adjustment

Abstract: Coparenting between biological parents is a strong predictor of child adjustment. To date, however, little is known about the coparenting dynamics between parent and stepparent in stepfamilies. This study aimed at exploring the links between coparenting in the mother-stepfather dyad and child behavior in stepfamilies compared with the links between mother-father coparenting and child behavior in first-marriage families. Two modes of coparenting were assessed: overt coparenting, that is, coparental behaviors in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 61 publications
0
16
0
Order By: Relevance
“…Among heterosexual couples, research has underscored distinct coparenting roles of mothers versus fathers, such as greater associations between contextual influences (e.g., work hours and satisfaction) and coparenting quality among mothers versus fathers, or gender differences in associations between parenting roles and children’s behavioral adjustment (e.g., unique links between maternal sensitivity and daughters’ adjustment as well as between paternal sensitivity and sons’ adjustment; Cowan et al, 1993; Riina & Feinberg, 2018; Zvara, Sheppard, & Cox, 2018). Moreover, associations between coparenting and child adjustment have been demonstrated among families in which at least one parent is not biologically related to the child (i.e., stepparent families; Favez, Widmer, Frascarolo, & Doan, 2019). Thus, new information about two critical areas relevant to coparenting and child development could be yielded from longitudinal studies including LG and adoptive parent family samples, respectively: (a) the relative role of parental gender and sexual orientation over time in families with parents diverse in sexual orientation (i.e., lesbian, gay, and heterosexual parents), and (b) whether associations between coparenting and child adjustment uncovered previously are also apparent over time among adoptive families (i.e., in the absence of any parent–child biological ties).…”
Section: Family Systems Theory Coparenting and Associations With Chil...mentioning
confidence: 99%
See 2 more Smart Citations
“…Among heterosexual couples, research has underscored distinct coparenting roles of mothers versus fathers, such as greater associations between contextual influences (e.g., work hours and satisfaction) and coparenting quality among mothers versus fathers, or gender differences in associations between parenting roles and children’s behavioral adjustment (e.g., unique links between maternal sensitivity and daughters’ adjustment as well as between paternal sensitivity and sons’ adjustment; Cowan et al, 1993; Riina & Feinberg, 2018; Zvara, Sheppard, & Cox, 2018). Moreover, associations between coparenting and child adjustment have been demonstrated among families in which at least one parent is not biologically related to the child (i.e., stepparent families; Favez, Widmer, Frascarolo, & Doan, 2019). Thus, new information about two critical areas relevant to coparenting and child development could be yielded from longitudinal studies including LG and adoptive parent family samples, respectively: (a) the relative role of parental gender and sexual orientation over time in families with parents diverse in sexual orientation (i.e., lesbian, gay, and heterosexual parents), and (b) whether associations between coparenting and child adjustment uncovered previously are also apparent over time among adoptive families (i.e., in the absence of any parent–child biological ties).…”
Section: Family Systems Theory Coparenting and Associations With Chil...mentioning
confidence: 99%
“…Observational data are particularly warranted in assessments of dyadic or triadic relationships, such as in the case of evaluating the quality of coparenting interaction through systematic coding; such procedures have yielded data revealing distinct linkages between overt coparenting and child outcomes among heterosexual parent families (Favez et al, 2019; Teubert & Pinquart, 2010). In addition, studies among heterosexual parent families have indicated the importance of examining coparenting quality over children’s development from early to middle childhood (Belsky & Hsieh, 1998; Martin, Ryan, Riina, & Brooks-Gunn, 2017; Umemura et al, 2015), and frequently include a combination of observational and self-report data (Brown, Schoppe-Sullivan, Mangelsdorf, & Neff, 2010; McHale, Kuersten-Hogan, Lauretti, & Rasmussen, 2000).…”
Section: Coparenting Among Lesbian and Gay Parentsmentioning
confidence: 99%
See 1 more Smart Citation
“…At first, studying co‐parenting allowed researchers to describe the importance of divorced parents' relationship quality for their children (e.g., Maccoby & Mnookin, 1992). Subsequently, the concept was applied to intact families as diverse as classic nuclear families, single parents, or same‐sex parents (Favez, Widmer, Frascarolo, & Doan, 2019; McHale & Lindahl, 2011).…”
mentioning
confidence: 99%
“…This study addressed several gaps in family systems research, primarily by including a sample of LG adoptive parent families, observations of family interaction, and analyses about how family dynamics may be associated with children's behavioral and adoption-specific outcomes. We used a multi-method, multi-informant design with observational data and reports from children and parents to minimize self-report bias and directly examine family behaviors; previous research has demonstrated the importance of observational data (in addition to, or beyond self-report data) to more comprehensively assess dyadic and triadic family interaction patterns and associations with children's adjustment (Favez, Widmer, Frascarolo, & Doan, 2019;Teubert & Pinquart, 2010).…”
Section: The Current Studymentioning
confidence: 99%